Adição de diferentes fontes de carbono no BFT para a produção de juvenis de tambaqui (Colossoma macropomum) - Naiara Pinho Alves (2022)
The expressive productivity of Colossoma macropomum is attributed to its favorable characteristics such as good acceptance of commercial rations, rusticity, good zootechnical performance and acceptance of its meat in the market The implementation of production systems capable of providing biosecurity are alternatives capable of using the minimum of water resources and reduce environmental impact. Among these systems is the biofloc technology (BFT), whose principle for its formation is the addition of an external source of organic carbon based on the carbon: nitrogen (C:N) ratio, stimulating the production of heterotrophic bacteria. Thus, the present work aimed to evaluate the effect of different carbon sources on the production of tambaqui (C. macropomum) in a biofloc system, since studies have shown that different sources of organic carbon added to BFT influence the development of system, stimulating the growth of the bacterial community, also conferring different characteristics of the biofloc, parameters of water quality, growth performance or well-being of the species produced. The experiment was carried out for 85 days at the Aquaculture Laboratory (LAQUA) of the Veterinary School of the Federal University of Minas Gerais-UFMG, Brazil. Using a completely randomized design in two types of systems: BFT and water recirculation (RAS) in clear water (AC). In the BFT systems, three different carbon sources were used as treatment, in quadruplicate: Wheat bran (25%) + Crystal sugar (75%), Starch and Crystal sugar. Water quality parameters such as OD (mg/L), temperature (ºC), TAN (mg//L), N-NO2- (mg/L), pH, alkalinity (mg CaCO3/L) and SS (ml/L) showed significant differences between treatments (p < 0.05), except for SST (ml/L). The data show statistical differences in the zootechnical performance of C. macropomum in the nursery stage for final weight, length, biomass and GP (p<0.05). Carbohydrate sources interfere in the zootechnical performance of C. macropomum fingerlings, and crystal sugar is recommended for this phase, according to the results obtained in this study, as it provided, as well as the system, of clear water, the best results in relation to final weight, weight gain and biomass.